the media treatment of the subject of women in the women's press in Algeria (Magazine"" maouid hawa"" model) - kechida, salima (Journal of Social Sciences and Humanities, 2025)
The media means have worked on stimulating different cases related in woman. Although the develpment that touched the communication world, the media haven’t yet reflected the reality of the woman situation generally and in particular the Algerian woman. Here, we work on identifying how the media treats the woman cases in algerian feminine press. The importance of this research appears in studying the relationship between woman and the media, how do both iteract and how the media takes the responsibility to evaluate the woman role in the society. Scientifcly, the woman’s role has remained or looks, sometimes, absent or barely existing. Sometimes, the woman appears in the media speeches and interviews but represents jut a picture no more. Our study is concluded with recognizing that the line on which the feminine press rolles in Algeria is a line that leads the woman out of the social, political, cultural and religious limits of the development of the Algerian society.